PENINGKATAN KUALITAS PEMBELAJARAN PKn DI SEKOLAH DASAR MELALUI MODEL PENGAJARAN BERMAIN PERAN - Norman Syam (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This classroom action research is intended to improve instructional quality in the subject of Pancasila and Kewarganegaraan (PKn) at primary school. The main focus of this research is to discover if role play model can be implemented to improve the quality of PKn. The research, conducted at the fifth grade in Primary School 5, Municipality of Bengkulu, used observation, open interview, and field note techniques in collecting data to be analyzed qualitively. The findings show that role play model can improve the instructional quality of PKn in Primary School. Therefore it is recommended the roleplay model to be applied at 3rd through 4th grades for more learning experiences.